Necrotizing Fasciitis of the Breast Requiring Emergent Radical Mastectomy. Issue 1 (16th September 2016) - Ward, Nicholas D.; Harris, Jennifer W.; Sloan, David A.
Abstract: Necrotizing fasciitis is a rare, aggressive, soft‐tissue infection that results in necrosis of skin, subcutaneous tissue, and fascia. It spreads rapidly and may progress to sepsis, multi‐organ failure, and death. Predisposing conditions include diabetes, chronic alcoholism, advanced age, vascular disease, and immunosuppression and many cases are preceded by an injury or invasive procedure. Necrotizing soft‐tissue infection of the breast is uncommon, with only a few reported cases in the literature. We present a 53‐year‐old diabetic woman who presented to the emergency room with several weeks of worsening breast and shoulder pain, swelling, and erythema. Upon formal evaluation by the surgical service, a necrotizing soft‐tissue infection was suspected, and the patient was scheduled for emergent, surgical debridement. Because of the aggressive nature and high mortality of this disease, immediate surgical intervention, coupled with antibiotic therapy and physiologic support, is necessary to prevent complications and death.